Effects of squat training with different depths on lower limb muscle volumes - Kubo, K.; Ikebukuro, T.; Yata, H. (European Journal of Applied Physiology, 2019)
Purpose: The purpose of this study was to compare the effects of squat training with different depths on lower limb muscle volumes.